The relationship between Helicobacter pylori and pityriasis versicolor - May H. El Samahy; Raafat Z. Abdelrahman; Hossam O. Ibrahim; Azza E. Mostafa (Journal of the Egyptian Women’s Dermatologic Society)
Background Although the immune dysregulation caused by Helicobacter pylori has been linked to the pathogenesis of many dermatological diseases, the link between H. pylori infection and pityriasis versicolor (PVC) has not been largely verified. Objective To study the probable association between active H. pylori infection and PVC prevalence and clinical parameters. Patients and methods The present case control study included 65 male patients with PVC (group A) and 65 dermatologically free patients (group B). Active H. pylori infection was detected in both groups using H. pylori stool antigen test (SAT). In group A, patients who tested SAT positive were subjected to measurement of anti-H. pylori immunoglobulin (Ig)G and IgA and interleukin (IL)-10 serum levels. Results The frequency of H. pylori was equal (61.5%) in both study groups. The various clinical parameters of PVC did not significantly differ between SAT-positive and SAT-negative patients. In group A, H. pylori-infected patients had elevated IgG and IgA serum titer, while IL-10 level was in most cases (65%) low. No significant relation was detected between the H. pylori serological markers and the PVC clinical parameters. Conclusion Active H. pylori infection did not impact the prevalence or clinical features of PVC. Elevated H. pylori IgG and IgA levels did not vary differentially in relation to PVC clinical features. Moreover, serum IL-10 level in active H. pylori-infected patients with PVC was not elevated. Accordingly, its role as a systemic immunosuppressive cytokine predisposing for PVC was unverified in this study.